PERFORMANCE EVALUATION OF GENE EXPRESSION PROGRAMMING IN IMPEDANCE SPECTROSCOPY FOR SENSOR MODELLING - Ramos, Pedro M. (2012)
This paper describes the recent improvements in the use of gene expression programming and genetic algorithms in impedance spectroscopy, namely in sensor modelling. Insight is given in the inner workings of the gene expression programming while highlighting the proposed improvements. The performance of the improved algorithm is also analyzed. It is further validated by the successful application to measurements of a real sensor.